The importance of neutrophil-to-lymphocyte ratio before and after radiation in breast cancer patients - Raci Behar; Stojkovska Snezana; Bahtijari Meleq; Hodolli Gezim; Nafez Gazmend; Uka Burim; Rizaj Diellor (Forum of Clinical Oncology)
The purpose of this research is to analyze the neutrophil-to-lymphocyte ratio (NLR) to define prognostic factors in patients with breast cancer and to analyze the NLR values among stages, grades, and fractions.